2022
DOI: 10.1186/s12885-022-09741-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of osimertinib in EGFR-mutant non-small cell lung cancer with distant metastasis

Abstract: Background Osimertinib—the third-generation epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI)—has been widely used as a first-line treatment for patients with metastatic EGFR-mutant non-small cell lung cancer (NSCLC). Osimertinib demonstrated central nervous system activity in patients with brain metastasis; however, its efficacy against other distant metastatic organs, including bone and liver, remains unclear. Therefore, we retrospectively analyzed the clinical efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…In a subgroup analysis of 118 patients with metastatic NSCLC disease in the brain, this study reported a longer PFS with Osimertinib compared to 1st gen TKIs erlotinib/gefitinib and 2nd gen TKI afatinib (16.3 vs. 7.9 vs. 8.3 months respectively). An improvement in OS was also noted to be trending towards significance with the use of Osimertinib compared to erlotinib/gefitinib (not reached vs. 20.9 months, p = 0.0725) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a subgroup analysis of 118 patients with metastatic NSCLC disease in the brain, this study reported a longer PFS with Osimertinib compared to 1st gen TKIs erlotinib/gefitinib and 2nd gen TKI afatinib (16.3 vs. 7.9 vs. 8.3 months respectively). An improvement in OS was also noted to be trending towards significance with the use of Osimertinib compared to erlotinib/gefitinib (not reached vs. 20.9 months, p = 0.0725) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients with liver metastasis showed significantly shorter PFS and OS, consistent with those previous findings. A very recent real-world study comparing the efficacies of different EGFR-TKIs showed that osimertinib, a third-generation EGFR -TKI, was not superior over other TKIs in patients with liver metastasis, while it provided significant clinical benefits in patients with brain or bone metastasis [ 35 ]. The association between liver metastasis and poor prognosis has been consistently reported across different treatment settings, including immunotherapy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Lung cancer patients who harbor LM often have significantly shorter progression-free survival (PFS) and overall survival (OS) compared to those with distant metastases in other organs. 3,4 The epidermal growth factor receptor (EGFR) mutation is the most common targetable driver mutation in lung cancer. 5 In the past decade, EGFR-tyrosine kinase inhibitors (TKIs) were suggested as the first-line therapy for patients with EGFR mutant lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…5 In the past decade, EGFR-tyrosine kinase inhibitors (TKIs) were suggested as the first-line therapy for patients with EGFR mutant lung cancer. 4 In current clinical practice, the tissue biopsy is routinely used to evaluate the EGFR mutation status. 6 And the distant metastasis is an important alternative if the primary tumor is unavailable to be sampled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation